2011
DOI: 10.1126/scitranslmed.3002573
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity Causes Multisystem Organ Failure and Exacerbates Acute Pancreatitis in Obesity

Abstract: Obesity increases the risk of adverse outcomes during acute critical illnesses such as burns, severe trauma, and acute pancreatitis. Although individuals with more body fat and higher serum cytokines and lipase are more likely to experience problems, the roles that these characteristics play are not clear. We used severe acute pancreatitis as a representative disease to investigate the effects of obesity on local organ function and systemic processes. In obese humans, we found that an increase in the volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
443
3
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 353 publications
(480 citation statements)
references
References 91 publications
25
443
3
9
Order By: Relevance
“…It has been previously shown that ATP levels drop in response to LA over 1 hour. 35 Similar to the pattern of LDH leakage, and the previously published data, 11,35 LA and OA resulted in significantly lower ATP levels, whereas their corresponding EEs (LAEE and OAEE had higher levels ( Figure 1C). We also noted cytochrome c leakage to be more with the FAs than with the corresponding FAEEs ( Figure 1D).…”
Section: Faees Induce Less Acinar Injury Than the Parent Fas At Equimsupporting
confidence: 87%
See 4 more Smart Citations
“…It has been previously shown that ATP levels drop in response to LA over 1 hour. 35 Similar to the pattern of LDH leakage, and the previously published data, 11,35 LA and OA resulted in significantly lower ATP levels, whereas their corresponding EEs (LAEE and OAEE had higher levels ( Figure 1C). We also noted cytochrome c leakage to be more with the FAs than with the corresponding FAEEs ( Figure 1D).…”
Section: Faees Induce Less Acinar Injury Than the Parent Fas At Equimsupporting
confidence: 87%
“…As previously published, we noted maximal Ca i increase at 600 mmol/L, which is in the range noted in human pancreatic necrosis collections. 11,32 Consistent with the loss of Jm being associated with triggering cell death, there was a greater increase in the 530/590 emission ratio of JC-1 induced by LA and OA than by LAEE or OAEE (Figure 2, A and B) at equal concentrations. Similarly, LA and OA (Figure 2, C and D) did cause an increase in Ca i , but LAEE and OAEE did not.…”
Section: Faees Induce Less Acinar Injury Than the Parent Fas At Equimmentioning
confidence: 52%
See 3 more Smart Citations